'Defect-irrelevant-winding' no-insulation (RE)Ba2Cu3O7 − x pancake coil in conduction-cooling operation. (23rd June 2021) - Bong, Uijong; Kim, Jaemin; Bang, Jeseok; Park, Jeonghwan; Han, Ki Jin; Hahn, Seungyong
Abstract: This paper reports experiment and simulation results of a 'defect-irrelevant-winding (DIW)' no-insulation (NI) (RE)Ba2 Cu3 O7 −  x pancake coil operated in a conduction-cooling environment at temperatures lower than 77 K. The key idea of the DIW high-temperature superconductor (HTS) winding technique, firstly proposed in 2016, is to wind an NI pancake coil with HTS tapes, on purpose, containing multiple 'defects.' Using the defect (flawed) HTS tapes, we expect to significantly lower the construction cost of a DIW HTS magnet in marginal sacrifice of the magnet performance. In this study, charging tests of a DIW coil were performed in a conduction cooling system by controlling the temperature of the second stage in a range of 20–65 K, to determine the maximum operable current that avoids thermal runaway of the test coil at a given temperature. Coil terminal voltages, center fields, local temperatures, and power supply currents were carefully monitored during the tests, and the trend for each parameter was obtained. Also, by use of an equivalent circuit model, the test results were numerically analyzed to evaluate the effect of local defects on the overall performance of the test coil in order to validate the feasibility of the DIW HTS coil in operation under the conduction-cooling environment at temperatures lower than 77 K.